2001
DOI: 10.1074/jbc.m008813200
|View full text |Cite
|
Sign up to set email alerts
|

Transcytosis of Lipoprotein Lipase across Cultured Endothelial Cells Requires Both Heparan Sulfate Proteoglycans and the Very Low Density Lipoprotein Receptor

Abstract: Lipoprotein lipase (LPL)1 is a 120-kDa dimeric protein that associates with the luminal surface of endothelial cells in multiple organs but especially in cardiac and skeletal muscle and in adipose tissue (1). This enzyme hydrolyzes the triglyceride in circulating lipoproteins such as chylomicrons and VLDL and produces free fatty acids that are used for metabolic energy or for fat storage. Endothelial cells do not synthesize LPL; rather myocytes and adipocytes produce it. Thus, it is a protein that requires tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
61
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 87 publications
(64 citation statements)
references
References 47 publications
3
61
0
Order By: Relevance
“…VLDL receptor knockout mice were always segregated with the retinal angiogenesis and subretinal neovascularization (53). On the other hand, it seems that endothelial cells are important sites for VLDL receptor because the movement of active LPL across endothelial cells involves both heparan sulfate proteoglycan and VLDL receptor, and VLDL receptor knockout mice showed lower plasma LPL activity, though the exact mechanism is under investigation (37,54).…”
Section: Novel Functions Of Vldl Receptormentioning
confidence: 99%
“…VLDL receptor knockout mice were always segregated with the retinal angiogenesis and subretinal neovascularization (53). On the other hand, it seems that endothelial cells are important sites for VLDL receptor because the movement of active LPL across endothelial cells involves both heparan sulfate proteoglycan and VLDL receptor, and VLDL receptor knockout mice showed lower plasma LPL activity, though the exact mechanism is under investigation (37,54).…”
Section: Novel Functions Of Vldl Receptormentioning
confidence: 99%
“…Based on these studies, it has initially been suggested that the VLDLr could play a role in the peripheral binding and subsequent internalization of TG-rich lipoproteins (4,5). More recently, Obunike et al (7) showed in vitro that the VLDLr is involved in the transcytosis of active LPL across endothelial cells. Therefore, it is now believed that the VLDLr may possibly function mainly by facilitating the binding of TG-rich lipoproteins in the capillary bed in concert with LPL, leading to the subsequent delivery of TG-derived FFAs to the underlying tissues active in FFA metabolism (5,8).…”
mentioning
confidence: 99%
“…LPL is synthesized in most extrahepatic tissues where it is transported to the endothelium (1, 2), a process dependent on heparan sulfate proteoglycans (HSPG) and the very low density lipoprotein (VLDL) receptor (3). There, LPL hydrolyzes triglycerides (TGs) in chylomicrons and VLDL, thereby generating free fatty acids that enter either storage or oxidative pathways.…”
mentioning
confidence: 99%